Composite solid electrolyte membrane and preparation method thereof
By combining inorganic and organic electrolytes in the solid electrolyte membrane and using plasticizers and dispersants, the problem of insufficient performance of the existing solid electrolyte membrane is solved, and higher ionic conductivity, better mechanical performance and better interface compatibility are achieved, improving the overall performance and safety of the battery.
Patent Information
- Application Number
- CN202411802435.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-12-09
AI Technical Summary
The existing solid electrolyte membranes have problems such as low ionic conductivity, poor solid interface compatibility, lithium dendrites growth, insufficient chemical and thermal stability, high material cost and difficult processing, difficult to balance the overall performance of the battery, and safety.
By combining the high strength of the inorganic solid electrolyte and the high ion mobility of the organic electrolyte, the synergistic action of the plasticizer and the dispersant is used to prepare a composite solid electrolyte membrane to improve ionic conductivity, improve mechanical properties and interface compatibility.
The ionic conductivity improvement, mechanical performance improvement and interface compatibility optimization of the solid electrolyte membrane are achieved, thereby enhancing the overall performance and safety of the battery.
Smart Images

Figure CN119560622A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of solid electrolyte preparation, and in particular relates to a composite solid electrolyte membrane and a preparation method thereof. Background Art
[0002] With the rapid development of portable electronic devices and electric vehicles, the demand for high energy density and high safety energy storage devices is becoming increasingly urgent. As a new type of electrolyte material, solid electrolytes have the advantages of high safety, high ionic conductivity, and wide electrochemical window, and have become a hot topic in current research.
[0003] At present, organic electrolytes have low ionic conductivity, inorganic electrolytes are brittle, have poor interfacial compatibility, and have complex preparation processes. Organic-inorganic composite solid electrolytes combine the advantages of organic and inorganic electrolytes and have good development prospects. However, in the preparation process, there are still certain problems in how to effectively disperse inorganic particles and improve the performance of electrolyte membranes. Summary of the invention
[0004] The present application provides a composite solid electrolyte membrane and its preparation method and application, aiming to solve the problems of existing solid electrolyte membranes, such as low ion conductivity, poor solid-solid interface compatibility, lithium dendrite growth, insufficient chemical and thermal stability, high material cost and difficulty in processing, difficulty in balancing the overall performance of the battery, and safety.
[0005] In a first aspect, the present application provides a composite solid electrolyte membrane, comprising the following raw materials in parts by weight: 80-120 parts of an inorganic solid electrolyte, 2-10 parts of an organic electrolyte, 0.1-0.3 parts of a dispersant, and 0.05-0.15 parts of a plasticizer.
[0006] The composite solid electrolyte membrane described in the present application combines the high strength of inorganic solid electrolytes and the high ion mobility of organic electrolytes, as well as the synergistic effect of plasticizers and dispersants, to achieve improved ionic conductivity, improved mechanical properties and optimized interface compatibility of the solid electrolyte membrane, thereby enhancing the overall performance and safety of the battery.
[0007] According to some embodiments of the composite solid electrolyte membrane described in the present application, the inorganic solid electrolyte includes one or more of lithium lanthanum zirconium titanate, lithium lanthanum zirconium oxide, lithium phosphorus oxynitride and lithium lutetium yttrium titanate.
[0008] According to some embodiments of the composite solid electrolyte membrane described in the present application, the organic electrolyte includes one or more of polyethylene oxide, polyvinylidene fluoride, polymethyl methacrylate and polyacrylonitrile.
[0009] According to some embodiments of the composite solid electrolyte membrane described in the present application, the dispersant includes one or more of a surfactant, a coupling agent, polyacrylonitrile and polystyrene sulfonic acid.
[0010] According to some embodiments of the composite solid electrolyte membrane described in the present application, the plasticizer includes one or more of ethyl cellulose, polyvinylidene fluoride, nanocellulose and graphene.
[0011] According to some embodiments of the composite solid electrolyte membrane of the present application, the number average molecular weight of the polyethylene oxide is 9×10 4 -11×10 4 .
[0012] According to some embodiments of the composite solid electrolyte membrane described in the present application, the surfactant includes polyvinyl pyrrolidone.
[0013] According to some embodiments of the composite solid electrolyte membrane described in the present application, the coupling agent includes γ-(2.3 glycidyloxy)propyltrimethoxysilane.
[0014] The second aspect of the present application provides a method for preparing the composite solid electrolyte membrane according to the first aspect of the present application, comprising the following steps:
[0015] (1) mixing an inorganic solid electrolyte, a dispersant and a solvent to obtain a mixed solution, and ball milling the mixed solution to obtain an inorganic solid electrolyte slurry;
[0016] (2) mixing an organic electrolyte, a plasticizer and the inorganic solid electrolyte slurry to obtain an organic-inorganic composite solid electrolyte slurry;
[0017] (3) coating the organic-inorganic composite solid electrolyte slurry on a release film, drying it, and peeling it off to obtain a composite solid electrolyte membrane.
[0018] The preparation method described in the present application improves the dispersibility of inorganic solid electrolytes in organic electrolytes by adding dispersants during ball milling, effectively reducing agglomeration, thereby improving the ionic conductivity and mechanical properties of the electrolyte membrane. At the same time, the addition of dispersants also improves the interface characteristics of inorganic solid electrolytes and optimizes the interface compatibility problem. The introduction of plasticizers and organic electrolytes further enhances the flexibility and ionic conductivity of the electrolyte membrane. By combining the high strength of inorganic solid electrolytes and the high ion mobility of organic electrolytes, this composite solid electrolyte membrane achieves an increase in ionic conductivity, an improvement in mechanical properties, and an optimization of interface compatibility, thereby enhancing the overall performance and safety of the battery.
[0019] According to some embodiments of the preparation method described in the present application, in step (1), the solvent includes one or more of acetonitrile, acetone, N-methylpyrrolidone and N,N-dimethylformamide.
[0020] According to some embodiments of the preparation method described in the present application, the solid content in the mixed solution is 60%-80%.
[0021] According to some embodiments of the preparation method described in the present application, the particle size of the inorganic solid electrolyte is 0.8-3 um.
[0022] According to some embodiments of the preparation method described in the present application, the temperature of the ball milling is 20-40° C., the rotation speed of the ball milling is 800-1200 rpm, and the time of the ball milling is 2-6 h.
[0023] According to some embodiments of the preparation method described in the present application, the particle size of the solid matter in the inorganic solid electrolyte slurry is 0.2-0.4 um.
[0024] According to some embodiments of the preparation method described in the present application, the ball milling media used in the ball milling includes one or more of zirconium oxide grinding balls, aluminum oxide grinding balls, silicon carbide grinding balls and silicon nitride grinding balls.
[0025] According to some embodiments of the preparation method described in the present application, the amount of the ball milling medium is 1 / 4-1 / 5 of the mass of the inorganic solid electrolyte.
[0026] According to some embodiments of the preparation method described in the present application, in step (2), the mixing temperature is 20-40° C., the mixing speed is 300-600 rpm, and the mixing time is 0.5-5 h.
[0027] According to some embodiments of the preparation method described in the present application, the viscosity of the organic-inorganic composite solid electrolyte slurry is 200-5000 mPas.
[0028] According to some embodiments of the preparation method described in the present application, the solid content of the organic-inorganic composite solid electrolyte slurry is 55%-70%.
[0029] According to some embodiments of the preparation method described in the present application, in step (3), the release film is a PET release film.
[0030] According to some embodiments of the preparation method described in the present application, the drying temperature is 90-100° C., and the drying time is 6-8 hours.
[0031] According to some embodiments of the preparation method described in the present application, the thickness of the composite solid electrolyte membrane is 30-150 um.
[0032] The third aspect of the present application provides a solid-state battery, comprising the composite solid-state electrolyte membrane described in the first aspect of the present application or the composite solid-state electrolyte membrane obtained by the preparation method described in the second aspect of the present application.
[0033] According to some embodiments of the solid-state battery described in the present application, the solid-state battery includes a solid-state lithium-ion battery or a solid-state lithium-sulfur battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 This is a schematic diagram of the structure of the composite solid electrolyte membrane during the electrochemical performance test described in this application. DETAILED DESCRIPTION
[0035] Embodiments of the present invention are described in detail below, and examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and intended to be used to explain the present invention, but should not be understood as limiting the present invention.
[0036] In the present invention, the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" etc. mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the described specific features, structures, materials or characteristics may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0037] The embodiment of the present application provides a composite solid electrolyte membrane, comprising the following raw materials in parts by weight: 80-120 parts of an inorganic solid electrolyte, 2-10 parts of an organic electrolyte, 0.1-0.3 parts of a dispersant, and 0.05-0.15 parts of a plasticizer.
[0038] The composite solid electrolyte membrane described in the present application combines the high strength of inorganic solid electrolytes and the high ion mobility of organic electrolytes, as well as the synergistic effect of plasticizers and dispersants, to achieve improved ionic conductivity, improved mechanical properties and optimized interface compatibility of the solid electrolyte membrane, thereby enhancing the overall performance and safety of the battery.
[0039] In some embodiments of the present application, the following raw materials are included in parts by weight: 90-110 parts of inorganic solid electrolyte, 4-5 parts of organic electrolyte, 0.15-0.25 parts of dispersant and 0.09-0.11 parts of plasticizer.
[0040] In some embodiments of the present application, the following raw materials are included in parts by weight: 95-105 parts of inorganic solid electrolyte, 4-5 parts of organic electrolyte, 0.18-0.23 parts of dispersant and 0.09-0.1 parts of plasticizer.
[0041] In some embodiments of the present application, the following raw materials are included in parts by weight: 100 parts of inorganic solid electrolyte, 5 parts of organic electrolyte, 0.2 parts of dispersant and 0.1 parts of plasticizer.
[0042] In some embodiments of the present application, the inorganic solid electrolyte includes one or more of lithium lanthanum zirconium titanate, lithium lanthanum zirconium oxide, lithium phosphorus oxynitride and lithium lutetium yttrium titanate.
[0043] In some embodiments of the present application, the organic electrolyte includes one or more of polyethylene oxide, polyvinylidene fluoride, polymethyl methacrylate and polyacrylonitrile;
[0044] In some embodiments of the present application, the dispersant includes one or more of a surfactant, a coupling agent, polyacrylonitrile and polystyrene sulfonic acid.
[0045] In some embodiments of the present application, the plasticizer includes one or more of ethyl cellulose, polyvinylidene fluoride, nanocellulose and graphene.
[0046] In some embodiments of the present application, the number average molecular weight of the polyethylene oxide is 9×10 4 -11×10 4 , can improve the ionic conductivity of the electrolyte membrane, optimize the processing performance, and ensure the uniformity and density of the membrane. Polyethylene oxide in this number average molecular weight range has high ionic conductivity. A higher molecular weight helps to form a better polymer chain network structure, thereby improving the mobility of lithium ions and enhancing the overall ionic conductivity of the electrolyte membrane. Polyethylene oxide in this molecular weight range makes the viscosity of polyethylene oxide in the solution moderate, which is convenient for processing and film formation, while ensuring the uniformity and density of the membrane and reducing the generation of defects.
[0047] In some embodiments of the present application, the surfactant includes polyvinyl pyrrolidone.
[0048] In some embodiments of the present application, the coupling agent includes γ-(2.3 glycidyloxy)propyltrimethoxysilane.
[0049] The present application also provides a method for preparing the composite solid electrolyte membrane according to the first aspect of the present application, comprising the following steps:
[0050] (1) mixing an inorganic solid electrolyte, a dispersant and a solvent to obtain a mixed solution, and ball milling the mixed solution to obtain an inorganic solid electrolyte slurry;
[0051] (2) mixing an organic electrolyte, a plasticizer and the inorganic solid electrolyte slurry to obtain an organic-inorganic composite solid electrolyte slurry;
[0052] (3) coating the organic-inorganic composite solid electrolyte slurry on a release film, drying it, and peeling it off to obtain a composite solid electrolyte membrane.
[0053] The preparation method described in the present application improves the dispersibility of inorganic solid electrolytes in organic electrolytes by adding dispersants during ball milling, effectively reducing agglomeration, thereby improving the ionic conductivity and mechanical properties of the electrolyte membrane. At the same time, the addition of dispersants also improves the interface characteristics of inorganic solid electrolytes and optimizes the interface compatibility problem. The introduction of plasticizers and organic electrolytes further enhances the flexibility and ionic conductivity of the electrolyte membrane. By combining the high strength of inorganic solid electrolytes and the high ion mobility of organic electrolytes, this composite solid electrolyte membrane achieves an increase in ionic conductivity, an improvement in mechanical properties, and an optimization of interface compatibility, thereby enhancing the overall performance and safety of the battery.
[0054] In some embodiments of the present application, in step (1), the solvent includes one or more of acetonitrile, acetone, N-methylpyrrolidone and N,N-dimethylformamide.
[0055] In some embodiments of the present application, the solid content in the mixed solution is 60%-80%, for example 60%, 65%, 68%, 70%, 76%, 80%, etc. When the medium filling rate is higher than 50%, the increase in medium filling will promote the impact of the ball milling medium on the ball milling material, effectively shortening the ball milling time.
[0056] In some embodiments of the present application, the particle size of the inorganic solid electrolyte is 0.8-3um, for example, 0.8um, 1.2um, 1.6um, 2.3um, 2.7um, 3um, etc.
[0057] In some embodiments of the present application, the temperature of the ball mill is 20-40°C, for example, 20°C, 25°C, 28°C, 30°C, 32°C, 36°C, 40°C, etc., the rotation speed of the ball mill is 800-1200rpm, for example, 800rpm, 900rpm, 920rpm, 960rpm, 1000rpm, 1050rpm, 1200rpm, etc., and the ball milling time is 2-6h. Ball milling is carried out within the temperature range of 20-40°C to avoid thermal damage or grain growth of the material due to excessively high temperature. The rotation speed range of 800-1200rpm can provide sufficient energy to achieve effective grinding, while avoiding excessive material crushing or equipment wear caused by excessive rotation speed, and reasonable ball milling time can ensure the uniformity and refinement of the material while maintaining production efficiency.
[0058] In some embodiments of the present application, the particle size of the solid matter in the inorganic solid electrolyte slurry is 0.2-0.4um, for example, 0.2um, 0.3um, 0.35um, 0.4um, etc. The solid electrolyte prepared from the solid electrolyte powder with small particle size has high purity and good dispersibility, and can effectively improve the conductivity.
[0059] In some embodiments of the present application, the ball milling media used in the ball milling includes one or more of zirconium oxide grinding balls, aluminum oxide grinding balls, silicon carbide grinding balls and silicon nitride grinding balls.
[0060] In some embodiments of the present application, the amount of the ball milling medium is 1 / 4-1 / 5 of the mass of the inorganic solid electrolyte.
[0061] In some embodiments of the present application, in step (2), the mixing temperature is 20-40°C, for example, 20°C, 25°C, 30°C, 32°C, 40°C, etc., the mixing speed is 300-600rpm, for example, 300rpm, 350rpm, 400rpm, 450rpm, 520rpm, 560rpm, 600rpm, etc., and the mixing time is 0.5-5h.
[0062] In some embodiments of the present application, the viscosity of the organic-inorganic composite solid electrolyte slurry is 200-5000mPas, for example, 200mPas, 500mPas, 1000mPas, 1600mPas, 2100mPas, 2700mPas, 3300mPas, 3800mPas, 4300mPas, 4900mPas, 5000mPas, etc. Within this viscosity range, the electrolyte slurry has good fluidity and processability.
[0063] In some embodiments of the present application, the solid content of the organic-inorganic composite solid electrolyte slurry is 55%-70%, for example, 55%, 60%, 68%, 70%, etc.
[0064] In some embodiments of the present application, in step (3), the release film is a PET release film.
[0065] In some embodiments of the present application, the drying temperature is 90-100°C, such as 90°C, 95°C, 98°C, 100°C, etc., and the drying time is 6-8h.
[0066] In some embodiments of the present application, the thickness of the composite solid electrolyte membrane is 30-150um, for example, 30um, 50um, 80um, 120um, 136um, 150um, etc.
[0067] An embodiment of the present application also provides a solid-state battery, comprising the composite solid electrolyte membrane described in the first aspect of the present application or the composite solid electrolyte membrane obtained by the preparation method described in the second aspect of the present application.
[0068] In some embodiments of the present application, the solid-state battery includes a solid-state lithium-ion battery or a solid-state lithium-sulfur battery.
[0069] The technical solution of the present application is further described below in conjunction with specific embodiments and drawings.
[0070] Example 1
[0071] A method for preparing a composite solid electrolyte membrane comprises the following steps:
[0072] Step 1: Preparation of inorganic solid electrolyte slurry
[0073] An inorganic solid electrolyte lithium lanthanum zirconium titanate (LLZTO) with a particle size of 0.8um is added to an acetonitrile (ACN) solution containing a dispersant polyacrylonitrile (PAN) to make the solid content in the mixed solution 70%; wherein the amount of polyacrylonitrile (PAN) in the solution is 0.2% of the mass of the inorganic solid electrolyte, and the LLZTO solid electrolyte is ball-milled using a high-speed dispersion ball mill, the ball milling medium used is zirconium oxide grinding balls, the amount of the ball milling medium is 1 / 4 of the mass of the inorganic solid electrolyte, the ball milling speed is controlled at 1000rpm, the ball milling temperature is controlled at 35°C, the ball milling dispersion time is 4h, and an inorganic solid electrolyte slurry is obtained, and the particle size of the solid matter in the inorganic solid electrolyte slurry is 0.2-0.4um.
[0074] Step 2: Preparation of organic-inorganic composite solid electrolyte slurry
[0075] The organic electrolyte polyethylene oxide (PEO) (number average molecular weight is about 100,000) and the above-mentioned inorganic solid electrolyte slurry are stirred and mixed at a temperature of 30°C and a rotation speed of 450rpm for 4 hours to fully dissolve the organic electrolyte, wherein the amount of organic electrolyte polyethylene oxide added is 5% of the mass of the inorganic solid electrolyte. After the organic electrolyte is fully dissolved, the plasticizer ethyl cellulose is added and mixed evenly, and the amount of the plasticizer added is 0.1% of the mass of the inorganic solid electrolyte to obtain an organic-inorganic composite solid electrolyte slurry. Acetonitrile solution is added to adjust the solid content of the composite solid electrolyte slurry to 65% and the viscosity to 500mPas.
[0076] Step 3: Preparation of organic-inorganic composite solid electrolyte membrane
[0077] Use PET release film as foil, and use an extrusion coater to coat the organic-inorganic composite solid electrolyte slurry described in step 2 on the smooth surface of the PET release film, and bake it at 95°C for 6 hours to obtain a composite solid electrolyte electrode. Then use a stacking stripping device to strip the composite solid electrolyte electrode to obtain an organic-inorganic composite solid electrolyte membrane with a thickness of 80um.
[0078] Example 2
[0079] The preparation method of the composite solid electrolyte membrane described in Example 3 is different from that in Example 1 only in that the amount of organic electrolyte added is different, and the amount of organic electrolyte polyethylene oxide added is 2% of the mass of the inorganic solid electrolyte.
[0080] Example 3
[0081] The preparation method of the composite solid electrolyte membrane described in Example 3 is different from that in Example 1 only in that the amount of organic electrolyte added is different, and the amount of organic electrolyte polyethylene oxide added is 10% of the mass of the inorganic solid electrolyte.
[0082] Example 4
[0083] The preparation method of the composite solid electrolyte membrane described in Example 4 is different from that in Example 1 only in that the amount of plasticizer added is different, and the amount of plasticizer added is 0.5% of the mass of the inorganic solid electrolyte.
[0084] Example 5
[0085] The preparation method of the composite solid electrolyte membrane described in Example 5 is different from that in Example 1 only in that the amount of plasticizer added is different, and the amount of plasticizer added is 1.5% of the mass of the inorganic solid electrolyte.
[0086] Example 6
[0087] The preparation method of the composite solid electrolyte membrane described in Example 6 is different from that in Example 1 only in that the ball milling time is different, and the ball milling dispersion time is 2 hours to obtain an inorganic solid electrolyte slurry.
[0088] Example 7
[0089] The preparation method of the composite solid electrolyte membrane described in Example 7 is different from that in Example 1 only in that the milling time is different, the ball milling dispersion time is 6 hours, and an inorganic solid electrolyte slurry is obtained.
[0090] Comparative Example 1
[0091] The preparation method of the composite solid electrolyte membrane described in Comparative Example 1 is different from that of Example 1 only in that the inorganic solid electrolyte and the organic electrolyte are mixed and ball-milled. That is, the composite solid electrolyte membrane described in Comparative Example 1 is prepared by adding the inorganic solid electrolyte and the organic electrolyte together into an acetonitrile solution containing a dispersant polyacrylonitrile and ball-milling.
[0092] The specific operations are:
[0093] Step 1: Preparation of inorganic solid electrolyte slurry
[0094] An inorganic solid electrolyte lithium lanthanum zirconium titanate (LLZTO) with a particle size of 0.3um and an organic electrolyte polyethylene oxide (PEO) (number average molecular weight of about 100,000) are added to an acetonitrile (ACN) solution containing a dispersant polyacrylonitrile (PAN) to make the solid content in the mixed solution 70%; wherein the amount of polyacrylonitrile (PAN) in the solution is 0.2% of the mass of the inorganic solid electrolyte, and the amount of the organic electrolyte polyethylene oxide added is 5% of the mass of the inorganic solid electrolyte. The LLZTO solid electrolyte is ball-milled using a high-speed dispersion ball mill, the ball milling medium used is zirconium oxide grinding balls, the amount of the ball milling medium is 1 / 4 of the mass of the inorganic solid electrolyte, the ball milling speed is controlled at 1000rpm, the ball milling temperature is controlled at 35°C, the ball milling dispersion time is 4h, and an organic-inorganic solid electrolyte slurry is obtained, and the particle size of the solid matter in the organic-inorganic solid electrolyte slurry is 0.2-0.4um.
[0095] Add plasticizer ethyl cellulose to the above organic-inorganic solid electrolyte slurry and mix evenly. The amount of plasticizer added is 0.1% of the mass of the inorganic solid electrolyte to obtain a composite solid electrolyte slurry. Add acetonitrile solution to adjust the solid content of the composite solid electrolyte slurry to 65% and the viscosity to 500 mPas.
[0096] Step 2: Preparation of organic-inorganic composite solid electrolyte membrane
[0097] A PET release film is used as a foil material, and an extrusion coater is used to coat the organic-inorganic composite solid electrolyte slurry described in step 2 on the smooth surface of the PET release film, and the mixture is baked at 95°C for 6 hours to obtain a composite solid electrolyte electrode. The composite solid electrolyte electrode is then stripped using a stacking stripping device to obtain an organic-inorganic composite solid electrolyte membrane with a thickness of 80 um.
[0098] Comparative Example 2
[0099] The preparation method of the composite solid electrolyte membrane described in Comparative Example 2 is different from that in Example 1 only in that the inorganic solid electrolyte is not subjected to ball milling treatment, that is, the inorganic solid electrolyte, organic electrolyte, dispersant and plasticizer are mixed evenly to obtain an organic-inorganic composite solid electrolyte slurry.
[0100] The specific operations are:
[0101] Step 1: Preparation of inorganic solid electrolyte slurry
[0102] An inorganic solid electrolyte lithium lanthanum zirconium titanium oxide (LLZTO) with a particle size of 0.3 um and an organic electrolyte polyethylene oxide (PEO) (number average molecular weight of about 100,000) are added to an acetonitrile (ACN) solution containing a dispersant polyacrylonitrile (PAN) to make the solid content in the mixed solution 70%; wherein the amount of polyacrylonitrile (PAN) in the solution is 0.2% of the mass of the inorganic solid electrolyte, and the amount of the organic electrolyte polyethylene oxide added is 5% of the mass of the inorganic solid electrolyte, to obtain an organic-inorganic solid electrolyte slurry, and the particle size of the solid matter in the organic-inorganic solid electrolyte slurry is 0.2-0.4 um;
[0103] Add plasticizer ethyl cellulose to the above organic-inorganic solid electrolyte slurry and mix evenly. The amount of plasticizer added is 0.1% of the mass of the inorganic solid electrolyte to obtain an organic-inorganic composite solid electrolyte slurry. Add acetonitrile solution to adjust the solid content of the composite solid electrolyte slurry to 65% and the viscosity to 500 mPas.
[0104] Step 2: Preparation of organic-inorganic composite solid electrolyte membrane
[0105] A PET release film is used as a foil material, and an extrusion coater is used to coat the organic-inorganic composite solid electrolyte slurry described in step 2 on the smooth surface of the PET release film, and the mixture is baked at 95°C for 6 hours to obtain a composite solid electrolyte electrode. The composite solid electrolyte electrode is then stripped using a stacking stripping device to obtain an organic-inorganic composite solid electrolyte membrane with a thickness of 80 um.
[0106] The physical properties of the composite solid electrolyte membranes described in Examples 1-7 and Comparative Examples 1-2 of the present application are studied, and the results are shown in Table 1:
[0107] Table 1
[0108]
[0109]
[0110] Note: 72h viscosity mPas refers to the viscosity change of a material within 72 hours and is usually used to measure the stability and flow properties of a material.
[0111] The viscosity test method described in this application is carried out using a rotational viscometer. According to GB / T 2793.1-1995 "Determination of viscosity of adhesives Part 1: Rotational viscometer method", during the test, the sample is placed in the measuring container of the viscometer, and the viscosity value of the sample is calculated by measuring the rotation speed of the container and the torque generated.
[0112] 72h particle size um refers to the change in particle size of a material within 72 hours, and is usually used to evaluate the particle size stability of a material. Particle size refers to the size of the particle, measured in microns (um).
[0113] The particle size test of this application adopts laser diffraction measurement technology. According to GB / T 19077-2003 "Laser diffraction method for particle size analysis", during the test, the sample is introduced into the laser beam. After the laser is scattered by the particles, the scattered light signal is received by the detector, and the particle size distribution is then calculated.
[0114] Tensile strength MPa refers to the stress at which the material produces the maximum uniform plastic deformation. In a tensile test, the maximum tensile stress to which the specimen is subjected until it breaks is the tensile strength, and the result is expressed in MPa.
[0115] The tensile strength test of this application is carried out in accordance with GB / T 1040.3-2006 "Determination of tensile properties of plastics Part 3: Film and sheeting". During the test, the sample is made into a standard shape, and the sample is stretched to fracture using a universal material testing machine. The maximum tensile force and gauge length change are recorded, and the tensile strength and elongation at fracture are calculated.
[0116] As can be seen from Table 1: Examples 1-7 have smaller viscosity changes and particle size changes than Comparative Examples 1-2, which is beneficial to improving the charge and discharge efficiency, conductivity, cycle stability and safety of the battery, and is beneficial to improving battery performance. In addition, Examples 1-7 have higher tensile strength, which means that the composite electrolyte membrane is not easy to break when subjected to tensile force. For the electrolyte membrane, higher tensile strength helps to improve the safety and stability of the battery.
[0117] Study on the electrochemical properties of the composite solid electrolyte membranes described in Examples 1-7 and Comparative Examples 1-2 of the present application
[0118] Test method: Assemble a symmetrical cell with a stainless steel (SS) / solid-state membrane / stainless steel (SS) sandwich structure, and use an electrochemical workstation to test the AC impedance of the solid-state membrane within a certain temperature range. The test frequency is 10 5 –0.1Hz, amplitude 10mV. The material resistance R is obtained by analyzing the electrochemical impedance spectroscopy (EIS) spectrum, and then the ionic conductivity σ is calculated. The formula is: σ=L / RS, where L is the thickness of the electrolyte membrane and S is the area of the electrolyte membrane;
[0119] The composite solid electrolyte membrane is assembled with the LiFePO4 positive electrode and the metal Li negative electrode into a solid half-cell, and the battery assembly is carried out in an inert atmosphere glove box, including the metal lithium sheet, the negative electrode shell, the electrolyte membrane and the positive electrode sheet, the positive electrode shell, etc.; the negative electrode shell is placed flat on an insulating table, the metal lithium sheet is placed in the center of the negative electrode shell, and the lithium sheet is flattened with a tablet pressing mold; the electrolyte membrane ( Figure 1 ) is placed flat on the lithium sheet, and then the positive electrode sheet and gasket to be tested are assembled with the positive electrode shell in sequence; finally, the negative end of the assembled button battery is placed on the button battery sealing machine mold with the negative electrode facing up, and the sealing operation is performed. The assembled button battery is tested for the first discharge specific capacity under 0.1C constant current cycle at room temperature 25°C. After a certain number of cycles, the discharge capacity retention rate is tested to evaluate the battery's cycle stability.
[0120] The test results are shown in Table 2:
[0121] Table 2
[0122] Conductivity S / cm Capacity retention after 200 cycles Example 1 <![CDATA[9.42×10 -4 ]]> 98.59% Example 2 <![CDATA[9.05×10 -4 ]]> 98.18% Example 3 <![CDATA[8.90×10 -4 ]]> 98.05% Example 4 <![CDATA[9.27×10 -4 ]]> 98.35% Example 5 <![CDATA[9.30×10 -4 ]]> 98.27% Example 6 <![CDATA[8.45×10 -4 ]]> 98.02% Example 7 <![CDATA[9.36×10 -4 ]]> 98.42% Comparative Example 1 <![CDATA[6.27×10 -4 ]]> 93.45% Comparative Example 2 <![CDATA[3.55×10 -4 ]]> 91.67%
[0123] It can be seen from Table 2 that the composite electrolyte membranes of Examples 1-7 of the present invention exhibit high ionic conductivity, indicating that ions and electrons can move quickly in the battery, achieving faster charging and discharging rates. In terms of electrochemical stability, after 200 charge and discharge cycles, the capacity retention rate of the composite electrolyte membrane using Example 1 is still maintained at a high level of 98.59%, showing excellent electrochemical stability.
[0124] Although the above embodiments have been shown and described, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. Changes, modifications, substitutions and variations of the above embodiments by those of ordinary skill in the art are all within the scope of protection of the present invention.
Claims
1. A composite solid electrolyte membrane, characterized in that: The invention comprises the following raw materials in parts by weight: 80-120 parts of inorganic solid electrolyte, 2-10 parts of organic electrolyte, 0.1-0.3 parts of dispersant and 0.05-0.15 parts of plasticizer.
2. The composite solid electrolyte membrane according to claim 1, characterized in that: The inorganic solid electrolyte includes one or more of lithium lanthanum zirconium titanate, lithium lanthanum zirconium oxide, lithium phosphorus oxynitride and lithium lutetium yttrium titanate; and / or, the organic electrolyte comprises one or more of polyethylene oxide, polyvinylidene fluoride, polymethyl methacrylate and polyacrylonitrile; and / or, the dispersant comprises one or more of a surfactant, a coupling agent, polyacrylonitrile and polystyrene sulfonic acid; And / or, the plasticizer includes one or more of ethyl cellulose, polyvinylidene fluoride, nanocellulose and graphene.
3. The composite solid electrolyte membrane according to claim 2, characterized in that: The number average molecular weight of the polyethylene oxide is 9×10 4 -11×10 4 ; and / or, the surfactant comprises polyvinyl pyrrolidone; And / or, the coupling agent includes γ-(2.3 glycidoxy)propyltrimethoxysilane.
4. The method for preparing the composite solid electrolyte membrane according to any one of claims 1 to 3, characterized in that: The following steps are involved: (1) mixing an inorganic solid electrolyte, a dispersant and a solvent to obtain a mixed solution, and ball milling the mixed solution to obtain an inorganic solid electrolyte slurry; (2) mixing an organic electrolyte, a plasticizer and the inorganic solid electrolyte slurry to obtain an organic-inorganic composite solid electrolyte slurry; (3) coating the organic-inorganic composite solid electrolyte slurry on a release film, drying it, and peeling it off to obtain a composite solid electrolyte membrane.
5. The method for preparing a composite solid electrolyte membrane according to claim 4, characterized in that: In step (1), the solvent includes one or more of acetonitrile, acetone, N-methylpyrrolidone and N,N-dimethylformamide; And / or, the solid content of the mixed solution is 60%-80%; And / or, the particle size of the inorganic solid electrolyte is 0.8-3 um; And / or, the ball milling temperature is 20-40° C., the ball milling speed is 800-1200 rpm, and the ball milling time is 2-6 h; And / or, the particle size of the solid matter in the inorganic solid electrolyte slurry is 0.2-0.4 um.
6. The method for preparing a composite solid electrolyte membrane according to claim 5, characterized in that: The ball milling media used in the ball milling include one or more of zirconium oxide grinding balls, aluminum oxide grinding balls, silicon carbide grinding balls and silicon nitride grinding balls; And / or, the amount of the ball milling medium is 1 / 4-1 / 5 of the mass of the inorganic solid electrolyte.
7. The method for preparing a composite solid electrolyte membrane according to claim 4, characterized in that: In step (2), the mixing temperature is 20-40° C., the mixing speed is 300-600 rpm, and the mixing time is 0.5-5 h; And / or, the viscosity of the organic-inorganic composite solid electrolyte slurry is 200-5000 mPas; And / or, the solid content of the organic-inorganic composite solid electrolyte slurry is 55%-70%.
8. The method for preparing a composite solid electrolyte membrane according to claim 4, characterized in that: In step (3), the release film is a PET release film; And / or, the drying temperature is 90-100° C., and the drying time is 6-8 hours.
9. The method for preparing a composite solid electrolyte membrane according to claim 4, characterized in that: The thickness of the composite solid electrolyte membrane is 30-150 um.
10. A solid-state battery, characterized in that: A composite solid electrolyte membrane comprising the composite solid electrolyte membrane according to any one of claims 1 to 3 or a composite solid electrolyte membrane obtained by the preparation method according to any one of claims 4 to 9; Preferably, the solid-state battery comprises a solid-state lithium-ion battery or a solid-state lithium-sulfur battery.
Citation Information
Patent Citations
Inorganic-organic composite solid-state electrolyte film and processing technology thereof
CN108448169A
Modification method of ceramic diaphragm and application and coating process thereof in lithium battery
CN110379983A
Solid-state electrolyte and preparation method thereof, solid-state battery and electronic equipment
CN110556575A
Composite solid electrolyte slurry, film, preparation method and all-solid-state battery
CN112687945A
Organic-inorganic composite solid electrolyte diaphragm as well as preparation method and application thereof
CN116885386A